2022
DOI: 10.1002/tea.21772
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in high school students' STEM career expectations: An analysis based on multi‐group structural equation model

Abstract: Gender gaps in STEM fields have been studied for a long time, and the primary focus has been on the relationship among social support (parents and teachers), STEM beliefs (STEM interest belief, self‐efficacy belief, and value belief), and STEM career expectations. Framed in Expectancy‐Value Models, this article aimed to explore how social support affects students' STEM career expectations directly and indirectly through STEM beliefs. Further, a gender study was conducted to examine the differences in structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…For example, students' emphasis on exploration of possible future selves through engagement with various STEM-related activities (taking action) aligns with previous scholarship (Burwell-Woo et al, 2015;Foster et al, 2019). The fact that students' active action-taking was heavily connected to their current interests in STEM also supports the key role of motivational factors such as personal interests in STEM participation (Gottlieb, 2018;Lv et al, 2022).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, students' emphasis on exploration of possible future selves through engagement with various STEM-related activities (taking action) aligns with previous scholarship (Burwell-Woo et al, 2015;Foster et al, 2019). The fact that students' active action-taking was heavily connected to their current interests in STEM also supports the key role of motivational factors such as personal interests in STEM participation (Gottlieb, 2018;Lv et al, 2022).…”
Section: Discussionmentioning
confidence: 81%
“…Research suggests that facets of identity exploration play a significant role in URMs' engagement with STEM in terms of future major/career aspirations and choices. These facets correspond to the identity exploration features discussed above, including (1) motivational constructs such as the interests and values one associates with STEM topics (e.g., Gottlieb, 2018;Lv et al, 2022), (2) STEM self-efficacy (e.g., Jiang et al, 2020;Turner et al, 2022), and (3) self-perceptions, or the ways a learner sees themself in STEM (e.g., Collins, 2018;Morton & Parsons., 2018). These identity-related constructs can be fostered by external factors such as social influences from family, friends, or mentors (e.g., Atkins et al, 2020;Tey et al, 2020), pre-college experiences with STEM (Miller et al, 2017;Phelps et al, 2018), exposure to STEM career knowledge (Blotnicky et al, 2018;Murcia et al, 2020), and campus environment (Castellanos, 2018).…”
Section: Identity Exploration In Stemmentioning
confidence: 99%
“…It has been reported that supplying information about STEM to parents improves their positive perceptions about this field and affects their children's future decisions about taking STEM courses, triggering their communication about the topic (Harackiewicz et al, 2012). Moreover, a recent study uncovered that parents' expectations and encouragement predict boys' STEM self-efficacy, which, in turn, is strongly correlated to STEM career expectations (Lv et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The lower number of women in STEM in comparison to men is a complex problem, in which many factors play a role (Blickenstaff, 2005;Brotman and Moore, 2008;Kelly, 2016;Lv et al, 2022). As this requires a holistic strategy to approach a solution, the effect of gender on students' decision of choosing science in general, and chemistry in particular, has been thoroughly studied at different levels in the last few decades.…”
Section: Gender Effects On the Choice Of Chemistrymentioning
confidence: 99%
“…Although STEM professionals are predominantly male, girls generally achieve higher grades in mathematics than boys. Higher grades are predictors of success in mathematics studies, which in turn is a strong indicator of success in STEM careers (Ly, Wang, Zheng, Peng, & Ping, 2022; Stoeger et al, 2013; Wang & Degol, 2017). Multiple studies investigating gender differences in math performance suggest comparable math ability, but slightly stronger female performance (Diekman et al, 2017; Lindberg et al, 2010; Voyer & Voyer, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%